Synthesis of Unsymmetrically Disubstituted Tetraphenylenes via Carbonyl-Directed C–H Functionalization - Pan, Shulei; Jiang, Hang; Zhang, Yu; Chen, Dushen; Zhang, Yanghui (Synlett, 2016)
A new strategy for the synthesis of unsymmetrically disubstituted tetraphenylenes from 2-acetylbiphenylene has been developed via ruthenium-catalyzed C–H functionalization. Four reactions, including alkenylation–cyclization, alkenylation, alkylation, and amidation, were achieved. The reactions provide easy access to a variety of unsymmetrically disubstituted tetraphenylene derivatives, which could accelerate research on the appliation of tetraphenylenes.
Keywords: tetraphenylene; C–H activation; palladium; alkenation; alkylation; amidation